2012
DOI: 10.1097/ijg.0b013e3182182897
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Visual Field Defects in Eyes With Different Optic Disc Appearances in Patients With Normal Tension Glaucoma

Abstract: The rate of progression of the field defects, the MD slope, in patients with NTG is possibly dependent on the baseline optic disc appearance. Thus, the optic disc appearance may be useful for the management of patients with NTG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 8 publications
4
18
0
Order By: Relevance
“…Furthermore, reliable methods for disc classification are also important, because of differing clinical characteristics in patients with each disc type (i.e., Nicolela’s 4 types) and the impact on the pattern of progress. [22, 30] However, classification of the ONH according to Nicolela’s methods is affected by variations arising from the subjectivity of judgments made based on funduscopic observations. [21] Thus, an objective, highly reproducible method for disc classification is an important goal for improving individual treatment of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reliable methods for disc classification are also important, because of differing clinical characteristics in patients with each disc type (i.e., Nicolela’s 4 types) and the impact on the pattern of progress. [22, 30] However, classification of the ONH according to Nicolela’s methods is affected by variations arising from the subjectivity of judgments made based on funduscopic observations. [21] Thus, an objective, highly reproducible method for disc classification is an important goal for improving individual treatment of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Follow-up investigations determined clinical characteristics associated with ONH morphological type in OAG patients, including the progression of visual field loss, differences in the structure/function relationship, the susceptibility to change in cpRNFLT, and various depth in anterior surface of lamina cribrosa. [2226] Thus, the importance of optic disc morphological characteristics lies in their relationship with clinical characteristics. However, assessment of the optic disc can sometimes be difficult because of the subjectivity of current examination techniques and variability between individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrences of rim notch, thinning of the local rim and enlargement of the ONH cup are especially important signs of risk [9]. In a previous study of glaucomatous ONH types using Nicolela's classification method, we found that the progression speed of glaucomatous visual field defects differed with ONH types [10]. Identifying certain patterns of glaucomatous ONH morphology may improve diagnostic accuracy and aid in identifying the effects of structural changes on visual function [11], [12].…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, macular lesions are often present in NTG. As we have previously demonstrated, the myopic disc type is more common in patients with NTG 11,12 and glaucoma patients with decreased visual acuity, 13 when patients are classified by optic disc type according to Nicolela's method. 14,15 In Japan, there is a high prevalence of myopia, which is associated with a high prevalence of myopia in NTG patients.…”
Section: Introductionmentioning
confidence: 78%